2018
DOI: 10.1111/cpr.12504
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA B4GALT1‐AS1 recruits HuR to promote osteosarcoma cells stemness and migration via enhancing YAP transcriptional activity

Abstract: We indicate that lncRNA B4GALT1-AS1 promotes OS cells stemness and migration via recruiting HuR to enhance YAP activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 33 publications
4
74
0
Order By: Relevance
“…been shown to regulate YAP activity [19,20,26], it is assumed that MALAT1 could regulate YAP transcriptional activity. As the transcriptional factor YAP plays a critical role in the expansion of CSCs and lncRNA has 2 GyÁmin À1 radiation followed by detecting the cell viability.…”
Section: Malat1 Directly Binds To Yap Enhances Yap Protein Expressiomentioning
confidence: 99%
“…been shown to regulate YAP activity [19,20,26], it is assumed that MALAT1 could regulate YAP transcriptional activity. As the transcriptional factor YAP plays a critical role in the expansion of CSCs and lncRNA has 2 GyÁmin À1 radiation followed by detecting the cell viability.…”
Section: Malat1 Directly Binds To Yap Enhances Yap Protein Expressiomentioning
confidence: 99%
“…LncRNAs could function by different pathways, such as lncRNAs serve as the protein co‐activators or co‐repressors, and thus the co‐regulators of mRNA and DNA . Recent studies have revealed the ceRNA roles of lncRNAs .…”
Section: Discussionmentioning
confidence: 99%
“…Originally, it was shown that a few lncRNAs are abnormally expressed in osteosarcoma (Li et al, 2013;Li et al, 2016). Subsequently, a large number of lncRNAs have been demonstrated to play an important role in the activities of osteosarcoma (Li et al, 2018;Huang et al, 2018;Deng et al, 2019). Furthermore, some lncRNAs have been demonstrated to be associated with the chemoresistance and overall survival of patients (Zhu et al, 2015;Chen et al, 2018;Chen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%